Prosocial Leadership and Creativity: How Perceived Social Proximity and Trust Shape Helping Behaviors and Response to Negative Feedback - Amna Manzoor (Journal of Management Practices, Humanities and Social Sciences, 2024)
Organizations' reactions to unfavourable managers input are garnering more and more scholarly and public attention. Thus far, the majority of the work has been on the prosocial motivation of organisational leaders, their impact on helpful behaviour, and the negative feedback that creativity targets. This study, which has its roots in trait activation theory, investigates how and to what degree prosocial motivation, perceived social proximity, and affect-based trust influence organisational leaders' helpful conduct and constructive criticism directed at innovation. We test our hypotheses on a sample of packing organisation leaders using two waves of original survey data, including a conjoint experiment. Our research adds to the body of knowledge on organisational prosocial motivation, negative feedback, and helping behaviour.